Meningkatkan Kualitas Hidup Lansia melalui Skrining Berat Badan di Tlogomas Malang - Nurul Evi; Achmad Masfi; Eri Yanuar Akhmad Budi Sunaryo; Yhenti Widjayanti; Muhammad Putra Ramadhan; Qory Tifani Rahmatika; Nurma Afiani; Ronal Surya Aditya (Jurnal Nusantara Mengabdi, 2023)
Purpose: The well-being of the elderly can be reflected in their health condition, both physically, spiritually and socially which enables everyone to live productively socially and economically. Modern lifestyles have changed human attitudes and behavior, including diet, smoking, consumption of alcohol and drugs as a lifestyle so that people with degenerative diseases (diseases caused by decreased organ function) are increasing and life threatening. The purpose of this community service is in the form of weight screening in the elderly. Methodology: The method used is measurement and examination as well as providing education. Methods for measuring body weight and conducting counseling about healthy lifestyles for the elderly in Tlogomas Village. Results: The results of the screening conducted, of the 55 participants who took part in the examination, found 29 normal people, 11 people had problems related to weight with obesity, and 15 people had problems less than normal. Conclusions: This Community Service Program runs smoothly and can provide benefits to the community. The results of this Community Service Program can be used as a reference for improving the health status of the elderly. Limitations: The area for community service is limited to the Tlogomas area. Contribution: This research is useful for the elderly in improving a healthy lifestyle in the gerontological area.